Barriers and perceptions of WHONET/BacLink adoption in Nepal: a qualitative study of clinical microbiology laboratories - Maharjan, Sanju; Gallagher, Patrick; Gautam, Manish; Gautam, Sanjay; Budhathoki, Manisha; Mukhiya, Reena; Kattel, Smirti; Bhandari, Amit; Joh, Hea Sun; Aboushady, Ahmed Taha; Zellweger, Raphaël M.; Upadhyaya, Madan Kumar; et al. (PLOS ONE, 2025)
Background The International Vaccine Institute-led CAPTURA (Capturing Data on Antimicrobial Resistance Patterns and Trends in Use in Regions of Asia) project delivered capacity building activities to strengthen antimicrobial resistance surveillance activities in Nepal. Methods The CAPTURA project trained 97 laboratory personnel from 19 hospitals on the use of WHONET/BacLink software to manage microbiology data in Nepal during 2020-2021. Approximately two years later, the trainees were followed up by phone to assess implementation status and effectiveness of the training. An inductive approach was used for coding and categorization of their response, and themes were generated for analysis. Trainees from ten hospitals agreed to respond regarding their experience. Results We found that two out of the ten hospitals were using the WHONET/BacLink software, with one each within and outside the national AMR surveillance network. The remaining eight hospitals never implemented the system despite receiving the training. Key barriers to implementation included, hospital administration prioritizing other interoperable software, limited ongoing training, inability to export data from an LIS, limited real-time assistance with technical issues, and poor confidence in analyzing data. In addition, limited human resources and minimal capacity-building activities resulted in a lack of confidence in using the system independently, which were also identified as barriers. Conclusion Implementing WHONET/BacLink software in hospital settings can be challenging due to various factors, including a lack of knowledge and confidence among users, a lack of time and human resources to use the software effectively, and a lack of interoperability with other hospital management systems. Real-time support and follow-up activities potentially reinforce the skills and knowledge delivered during the training.
Gesehen am 20.01.2026